Examination of Anxiety Levels Among First-line Healthcare Professionals in the February 2023 Türkiye Kahramanmaraş Earthquake - Kaan Yusufoğlu; İlker Akbaş; Sinem Doğruyol; İbrahim Altundağ; Metin Öner; Burcu Genç Yavuz (Global Emergency and Critical Care)
Objective: Two earthquakes of 7.7 and 7.6 magnitudes on the Richter scale occurred in Kahramanmaraş on February 6, 2023, resulting in 50,000 deaths and significant devastation. Our aim was to assess the anxiety levels of emergency healthcare professionals (HPs) providing medical services in earthquake-stricken areas following the Kahramanmaraş earthquake. Materials and Methods: This study included survivor and volunteer HPs. Only 89 of 159 HPs completed the questionnaire, resulting in a response rate of 57.1%. Results: The mean Beck anxiety inventory (BAI) score for survivor HPs was 29.53±13.25, and for volunteer HPs was 7.62±11.12. The average BAI score for all HPs working in the earthquake zone was 19. The difference between these scores was statistically significant (95% confidence interval: 16.77-27.05, p=0.000). Conclusion: Our study indicates that HPs providing first-line health services in earthquake-stricken areas exhibit high anxiety scores. The BAI scores of survivor HPs were higher than those of volunteer HPs. As the duration of work in earthquake-stricken areas increased, anxiety levels increased accordingly.